(untitled) (Indian Journal of Arid Horticulture, 2025)
Some fruit crops are monoecious in nature, while many others possess hermaphrodite flowers. On the contrary, certain fruit crops are dioecious. Various factors can affect effective pollination. Diploid plants produce abundant pollen; however, triploid plants fail to do so. Sometimes, flowers bloom earlier than the critical period of stigma receptivity, while in other cases, flowering may extend beyond the stigma’s receptive phase. Such variations disrupt the pollination process, making pollenization necessary.This article attempts to cover all such aspects of pollination and pollenization to enhance the understanding of these phenomena, ultimately improving fruit set.